But Where Will the Money Come From? Experts' Views on Revenue Options to Implement Campaign for Fiscal Equity v. State of New York - Osnat Zaken; Jeffery E. Olson (Educational Considerations, 2013)
In 2003, the New York State Court of Appeals, the highest court in New York, upheld a trial court decision that funding for public education in New York City was unconstitutional and decreed that the state needed to increase operating aid to school districts by $5.6 billion per year (Campaign for Fiscal Equity, Inc. v. State of New York 2003).
Keywords: recommendations; money; revenue; options; implement; New York; Campaign; Fiscal Equity; tax; Institute; policy